Genetic analysis of mRNA synthesis in adenovirus region E3 at different stages of productive infection by RNA-processing mutants. - Bhat, B M (1986)
Region E3 of adenovirus encodes about nine overlapping mRNAs (a to i) with different spliced structures and with two major RNA 3' end sites termed E3A and E3B. Synthesis of E3 mRNAs was examined by the nuclease-gel procedure at early and late stages of infection by wild-type virus (rec700) and by several E3 deletion mutants. Our results, together with those obtained by electron microscopy (L. T. Chow, T. R. Broker, and J. B. Lewis, J. Mol. Biol. 134:265-303, 1979), suggest that E3 may be differentially regulated at early and late stages at both the promoter and RNA-processing levels. Early after infection, the E3 promoter is used to make mainly mRNAs a and h. Late after infection, the E3 promoter appears to be shut off and the major late promoter is used to make mainly mRNAs d and e. The late L4 mRNA 3' end site is not used early even though early E3 pre-mRNAs transcribe through the L4 RNA 3' end site. The nucleotide 768-951 exon, which is the y leader on many L5 mRNAs, is very abundant late. (Nucleotide +1 is the major E3 transcription initiation site.) Early after infection, the 951 5' splice site is enhanced 5- to 10-fold in the dl712 (delta 1691 to 2122) group of mutants; late after infection, these mutants resemble the wild type. We speculate that the activity of the 951 5' splice site is regulated at early and late stages; it is suppressed early to permit synthesis of mRNA a, and it is activated late to permit synthesis of mRNAs d, e, and L5. With dl719 (delta 2173 to 2237), the 951----2157 splice is enhanced both early and late; we suggest that this deletion enhances the 2157 3' splice site.